PENGARUH SECONDARY SKIN PADA FASADE BANGUNAN TERHADAP KUALITAS CAHAYA ALAMI DAN PENGHAWAAN PADA RESTORAN BAKERY (Studi Kasus : Restoran J.Co Jatiwaringin) - Ahmad Aldi Alkindi Sitorus; Ayu Oktaviani (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2025)
This study examines the effect of applying a secondary skin to a building facade on the quality of natural light at the J.CO Donuts & Coffee restaurant in Jatiwaringin, Bekasi. Natural lighting is a crucial aspect of architectural design that directly impacts user visual comfort. The purpose of this study is to evaluate the extent to which the application of a secondary skin can control natural light intensity according to comfort standards based on SNI 6197-2020.The research method used was a quantitative approach with field observation techniques and light intensity measurements using a lux meter at several points within the restaurant space. The measurement data were then compared with the natural lighting standards set by SNI. The results showed that the application of the secondary skin on the facade was not fully optimal. The natural light intensity values at the first (489 LUX) and second (899 LUX) measurement points exceeded comfort standards, while the third point (211 LUX) almost met the established standards. The conclusion of this study indicates that the secondary skin design of the facade needs to be optimized to balance natural light intensity across the entire space. The addition of facade elements such as lattices or vines is recommended to help reduce excess light without reducing the overall quality of natural lighting